Biotechnologies for wildlife fertility preservation. (1st January 2015) - Comizzoli, Pierre
Abstract: Reproductive biotechnologies are still considered critical tools for saving and maintaining endangered species. Some successes have been reported with the use and integration of artificial insemination (with fresh or frozen-thawed samples) in conservation programs. However, not a single species is currently managed through oocyte freezing or embryo-based technologies. The limited contribution of fertility preservation techniques to species conservation principally stems from the lack of knowledge of species biology, as well as inadequate facilities, space, expertise, and funding needed for their successful application. More fundamental studies on animal reproductive biology as well as more fertility preservation options are needed with all parties involved (reproductive technologists, zoo biologists, and conservationists) adopting parallel efforts to sustain wild populations and habitats.